Opini Publik Followers Instagram Volix Media sebagai Media Pemenuhan Kebutuhan Informasi Publik - Abdullah, Haikal Syahid; Prananingrum, E. Nugrahaeni; Putri, Maulina Larasati; Putri, K.Y.S.; Sutjipto, Vera Wijayanti; Sary, Marisa Puspita (Universitas Medan Area, 2024)
This article aims to evaluate public opinion, specifically the followers of Instagram Volix Media, regarding the extent to which the information presented meets their needs. The issue under scrutiny pertains to Instagram Volix Media, which has been providing diverse information about Indonesian pop culture, music, film, artists, news, art, and little-known culture since 2021. To approach this issue, Cutlip & Center's theory on the characteristics of public opinion is employed, encompassing five dimensions: direction, intensity, stability, informational support, and social support. Data were collected by distributing questionnaires to 100 respondents who are followers of Instagram Volix Media. The data were analyzed using a quantitative approach and descriptive methods.The results indicate that the dimension of informational support received the highest average score, suggesting that respondents have more information on the issues presented. However, the dimension of social support received the lowest average score, indicating a lack of perceived support from others regarding the opinions expressed. This article concludes that Instagram Volix Media exhibits a positive direction of opinion, with the majority of respondents agreeing that the information presented meets the needs of public information.